Metal lability and environmental risk in anthropogenically disturbed Antarctic melt streams. (15th October 2021) - Koppel, Darren J.; Bishop, Jordan; Kopalová, Kateřina; Price, Gwilym A.V.; Brown, Kathryn E.; Adams, Merrin S.; King, Catherine K.; Jolley, Dianne F.
Abstract: Antarctic melt streams are important ecosystems that increasingly face contaminant pressures from anthropogenic sources. Metal contaminants are often reported in the limno-terrestrial environment but their speciation is not well characterised, making environmental risk assessments difficult. This paper characterises labile metal concentrations in five melt streams and three shallow lakes around the Casey and Wilkes research stations in East Antarctica using chemical extracts and field deployments of diffusive gradients in thin-film (DGT) samplers. An acute toxicity test with field-collected Ceratadon purpeus and taxonomic identification of diatoms in melt streams were used to infer environmental risk. Copper and zinc were the most labile metals in the melt streams. DGT-labile copper concentrations were up to 3 μg Cu L −1 in melt-stream waters but not labile below the sediment-water interface. DGT-labile zinc concentrations were consistent above and below the sediment-water interface at concentrations up to 14 μg Zn L −1 in four streams, but one stream showed evidence of zinc mineralisation in the sediment with a flux to overlying and pore waters attributed to the reductive dissolution of iron and manganese oxides. Other metals, such as chromium, nickel, and lead were acid-extractable from the sediments, but not labile in pore waters or overlying waters. All streams had unique compositions of freshwater diatoms, but one had particularly reduced diversity and richness, which correlated to metal contamination and sediment physico-chemical properties such as a finer particle size. In laboratory bioassays with field-collected samples of the Antarctic moss C. purpeus, there was no change in photosynthetic efficiency following 28-d exposure to 700, 900, 1060, or 530 μg L −1 of cadmium, copper, nickel, and zinc, respectively. This study shows that microorganisms such as diatoms may be at greater risk from contaminants than mosses, and highlights the importance of geochemical factors controlling metal lability. Graphical abstract: Image 1 Highlights: Metal lability in five Antarctic melt streams and three lakes were assessed. Copper and zinc are metals of concern owing to their lability in melt streams. Streams had unique compositions of diatoms with different richness and diversity indices. Melt-stream chemistry and labile metals correlated to diatom community differences. No acute toxicity from Cd, Cu, Ni, or Zn to a moss species was observed. Abstract : Copper and zinc are contaminants of concern in anthropogenically-impacted Antarctic melt stream sediments and waters due to their greater lability than other metals including lead and chromium. Microorganisms, such as diatoms, are more likely to experience toxic effects than habitat-forming mosses, which were resilient to high exposure concentrations of these metals.